Soft computing approach for predicting OPEC countries’ oil consumption - Chiroma, Haruna; Abubakar, Adamu; Herawan, Tutut (Inderscience, 2017)
Human activities in todays modern world would not be possible without energy. The energy consumed by the Organization of the Petroleum Exporting Countries (OPEC) has increased significantly. In this paper, a soft computing method is proposed for predicting oil consumption in OPEC countries. The significant, positive relationship among the oil consumption values of OPEC countries is also investigated. It was found that it is possible to predict the oil consumption of any OPEC country on the basis of the oil consumption of other OPEC countries with minimum and maximum accuracy of 94.6268% and 97.0994%, respectively. Statistical result validation clearly shows that the oil consumption predicted with the proposed model and the actual oil consumption are statistically equal. The findings of this research can be applied for the efficient formulation of policies related to energy. Furthermore, energy consumption prediction is required for the management of greenhouse emissions, the creation of effective risk management frameworks, and revenue generation analysis.